Hubungan antara kadar asam urat dengan tekanan darah pada anak obes di Kecamatan Talawaan Kabupaten Minahasa Utara - Sarundaitan, Herlin S.; Warouw, Sarah M.; Runtunuwu, Ari L. (e-CliniC, 2016)
Abstract: Obesity is an increasing global health problem in many countries. The most common causes are genetic factor, lack of physical activity as well as combinations of these factors. Uric acid is an end product of purine metabolism. Elevated uric acid level is influenced by various factors such as alcohol, genetic, hypothyroidism, obesity, and high-purine diet. In children all over the world, the increased prevalence of overweight and obesity influences the prevalence of hypertension, especially primary hypertension. This study aimed to determine the relationship between the level of blood uric acid and blood pressure among obese children. This was an observational analytical study. Samples were obtained by using consecutive sampling method. This study was conducted at Talawaan North Minahasa during October 2015-January 2016. There were 38 obese children aged 13-15 years as samples, consisted of 14 males and 24 females. The results showed that the majority of samples were in the age categories 13 and 14 years; each category consisted of 17 samples (44.7%). The lowest was age category of 15 years, consisted of 4 samples (10.5%). The mean systolic blood pressure was 123.16 mmHg (SD ± 12.967) and the mean diastolic blood pressure was 81.58 mmHg (SD ± 11.514). The mean level of blood uric acid was 4.858 mg/dL (SD ± .9328). The Pearson correlation statistical test for the relationship between uric acid level and systolic blood pressure showed a P value of 0.306 (r<0.02) and for the relationship between uric acid levels and diastolic blood pressure showed a P value of 0.152 (r <0.02). Conclusion: There was a positive relationship between the level of blood uric acid and blood pressure among obese children but not statistically significant. Keywords: uric acid, blood pressure, obesity Abstrak: Obesitas merupakan masalah kesehatan dunia yang semakin meningkat di berbagai negara. Penyebab yang paling sering menyebabkan obesitas ialah faktor genetik, kurangnya aktifitas fisik, serta kombinasi dari kedua faktor ini. Asam urat merupakan produk akhir metabolisme purin. Penyebab meningkatnya kadar asam urat dipengaruhi oleh berbagai macam faktor antara lain alkohol, genetik, hipotiroid, obesitas, dan diet tinggi purin. Pada populasi anak di seluruh dunia, peningkatan prevalensi kegemukan dan obesitas turut meningkatkan prevalensi hipertensi, terutama hipertensi primer. Penelitian ini bertujuan untuk mengetahui hubungan antara kadar asam urat dengan tekanan darah pada anak obes. Jenis penelitian ini analitik observasional dengan desain potong lintang. Sampel diperoleh dengan metode consecutive sampling. Penelitian ini dilakukan di Kecamatan Talawaan Kabupaten Minahasa Utara selama bulan Oktober 2015 – Januari 2016. Terdapat 38 anak obes berusia 13-15 tahun sebagai sampel, yang terdiri dari 14 anak laki-laki dan 24 anak perempuan. Hasil penelitian memperlihatkan bahwa sebagian besar responden berada pada kategori umur 13 dan 14 tahun masing-masing berjumlah 17 orang (44,7%), dan terendah umur 15 tahun sebanyak 4 orang (10,5%).Rerata tekanan darah sistol 123,16 mmHg (SD ± 12,967) dan rerata tekanan darah diastol 81,58 mmHg (SD ± 11,514). Rerata kadar asam urat responden 4,858 mg/dL (SD ± 0,9328). Uji statistik Pearson Correlation untuk hubungan antara kadar asam urat dengan tekanan darah sistol menunjukkan nilai P = 0,306 (r<0,02) dan untuk hubungan antara kadar asam urat dengan tekanan darah diastol menunjukkan nilai P = 0,152 (r <0,02). Simpulan: Terdapat hubungan positif antara kadar asam urat darah dengan tekanan darah pada anak obes namun secara statistik tidak bermakna.Kata kunci: asam urat, tekanan darah, obesitas